First evidence for the existence of pennate diatom viruses - Tomaru, Yuji (Nature Publishing Group, 2012)
Diatoms are considered the most successful and widespread group of photosynthetic eukaryotes. Their contribution to primary production is remarkably significant to the earth's ecosystems. Diatoms are composed of two orders: Centrales and Pennales. Thus far, viruses infecting centric diatom species have been isolated and characterized; however, viruses infecting pennates have not been reported. Here, we describe the first isolations and preliminary characterizations of two distinct pennate diatom viruses, AglaRNAV (31 nm in diameter, accumulates in the host cytoplasm) and TnitDNAV (35 nm in diameter, accumulates in the host nuclei) infecting Asterionellopsis glacialis and Thalassionema nitzschioides, respectively. Their genomes contain a single-stranded RNA of approximately 9.5 kb, and a closed, circular single-stranded DNA of approximately 5.5 kb harboring a partially double-stranded region, respectively. Further analysis of these viruses may elucidate many aspects of diatom host–virus relationships.